Rasionalitas Tindakan KH. Ahmad Dahlan dalam pengembangan Pendidikan Islam di Indonesia - Rahmat Abd Fatah (Departement of Mathematics Education, 2024)
This study aims to analyse the main ideas and forms of KH. Ahmad Dahlan's actions in the development of Islamic education in Indonesia, through the perspective of Max Weber's social action theory, namely instrumental rationality, value rationality, affective action, and traditional action. The novelty of this research is the application of Weber's social action theory analysis to the figure of Islamic reformers, which has not previously been discussed in depth in Islamic education literature. The method used is a literature study, in which various scientific articles and related literature are analysed to explore the thoughts and actions of KH Ahmad Dahlan. The results of the study show that KH Ahmad Dahlan successfully integrated aspects of rationality, values and tradition in educational reform, which was not only relevant in his time but also provides a strong foundation for Islamic education today. The recommendation of this study is the need for integration between traditional and modern values in the Islamic education curriculum as well as the application of a holistic and inclusive approach to education as pioneered by KH. Ahmad Dahlan.